Productivity Analysis Of Filling Machine With The Objective Matrix (OMAX) Method - Sinaga, Katrin; Lie, Kevin; Williams, Nico; Sunarni, Theresia (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
A Factory is a manufacturing industry that produces tea drinks in cups. A Factory is also inseparable from problems related to machine/equipment productivity. Based on the results of observations made at A Factory part of the production line that there is often a sudden stop of the production process. The discontinuation will affect the quality of the product expected and the production targets to be achieved. The problem was discussed in this research is how much the productivity level of the filling production department is, how much the production effectiveness, effective working hours, the number of defective products, and machine downtime criteria. The productivity measurement method used is the Objective Matrix (OMAX) method, so the steps of this study refer to OMAX steps, which is the criteria determination/productivity ratio of the production line, the calculation of the productivity ratio value, the calculation of the initial standard score (score 3), The determination of the goal (score 10) and the lowest score (score 0), the determination of weight, the calculation of value/criteria value, the determination of productivity value for each period, determination of index percentage. With the OMAX method, it can be seen that in period 11 (compared to period 10) there was an increase in productivity, this can be seen because the IP value (Index of Performance) which is positive (+) is 27.79 and there is an increase in the value of the calculation at the time of measurement (current) from 383.36 to 300. This increase was due to an increase in the value of all criteria.